2015
DOI: 10.1177/1029864915570355
|View full text |Cite
|
Sign up to set email alerts
|

When they listen and when they watch: Pianists’ use of nonverbal audio and visual cues during duet performance

Abstract: Nonverbal auditory and visual communication helps ensemble musicians predict each other’s intentions and coordinate their actions. When structural characteristics of the music make predicting co-performers’ intentions difficult (e.g., following long pauses or during ritardandi), reliance on incoming auditory and visual signals may change. This study tested whether attention to visual cues during piano–piano and piano–violin duet performance increases in such situations. Pianists performed the secondo part to thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 42 publications
5
63
0
6
Order By: Relevance
“…In addition, the regular rhythmical structure of the piece chosen for the study might have altered, or eliminated, any benefit arising from VC between singers. Previous research suggests eye cues are beneficial when irregular musical timings are being performed (28). However, the fact that NB synchronization was significantly better without VC between singers remains surprising, since previous research (19) has shown no effect of VC on median unsigned asynchronies, unlike an apparent benefit from performers not seeing each other.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In addition, the regular rhythmical structure of the piece chosen for the study might have altered, or eliminated, any benefit arising from VC between singers. Previous research suggests eye cues are beneficial when irregular musical timings are being performed (28). However, the fact that NB synchronization was significantly better without VC between singers remains surprising, since previous research (19) has shown no effect of VC on median unsigned asynchronies, unlike an apparent benefit from performers not seeing each other.…”
Section: Discussionmentioning
confidence: 50%
“…Synchronization between musicians is maintained through iterative temporal adjustments which might relate to expressive interpretations or noise during cognitivemotor processes. Research suggests that synchronization in small ensembles (17,18) might be affected by VC between musicians when auditory feedback is limited or musical timing is irregular, and by leader-follower relationships between members of a musical ensemble. However, how synchronization evolves during vocal ensemble performances in relation to these factors still needs to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Much less is known—scientifically or by performing arts organizations hoping to understand and build their audiences—about listeners' experience (what they think, feel and do during and after a performance) than about the demographic characteristics of audiences going to concerts or buying recordings (Radbourne et al, 2013a; see also chapters in Burland and Pitts, 2014). Investigations of differences in actor-observer experience and cognition (Jones and Nisbett, 1972; Malle et al, 2007, among many others) and important studies of musical communication (Williamon and Davidson, 2002; Hargreaves et al, 2005; Davidson, 2012; Loehr et al, 2013; Cross, 2014; Keller, 2014; Bishop and Goebl, 2015, among many others) have not directly focused on how performing musicians' ongoing mental life while performing connects and doesn't connect with listeners' ongoing mental life as they experience the performance. We see these questions as addressing broader and fundamental unknowns: when and with whom do our thoughts and/or feelings overlap, and when and with whom do they not—whether or not we think they do?…”
Section: Introductionmentioning
confidence: 99%
“…Application of this measure requires clarification, since usage in the literature varies significantly. For instance, Ragert et al (2013) refer to mean absolute asynchrony as a measure of synchronization 'accuracy', 5 distinguishing it from 'precision', while Bishop and Goebl (2015) use the same measure to judge how 'successful' synchronization was within duos, which could be interpreted as 'precision'. In fact, mean absolute asynchrony is highly correlated with asynchronization in our dataset (comparing results by 2-minute Segment, see following paragraph; r(58) = 0.939, p < .001), and therefore may be used as an alternative measure for 'precision'.…”
Section: Results 1: Sensorimotor Synchronizationmentioning
confidence: 99%